The abuse of polygamy in Malaysia: an analysis from Islamic perspective - Fatah Yasin, Raudlotul Firdaus; Jani, Mohd. Shah (IIUM Press, International Islamic University Malaysia, 2017)
This book aims at identifying the qualification, according to the Qur’ān and Sunnah of the Prophet (PBUH), which allows Muslims to practice polygamy and determining the consistency of reasons stated in polygamy applications at Shariah Courts, based on the original intents of Shari'ah legislation on polygamy. The book also analyzes the effectiveness of the existing SharÊÑah Law as preventive measurement to curb the abuse of polygamy, so as to propose practical means including institutional reforms derived from the Qur’Én and the living example of the Prophet’s Sunnah. This book uses the inductive method to organise all the Qur’anic verses and ahadith that enumerate the reasons for polygamy, the envisage problems and their solutions, coupled with traditional and modern scholars’ interpretations and commentaries. Field research and interviews were applied to gain the latest statistical records on polygamy applications from the year 2007 until 2009 which were obtained from the Kuala Lumpur and Selangor Shariah Courts. Library research was also used to analyze the accuracy of Islamic Family Law Act in comparison with the Qur’an and Sunnah legislation. Analytical and comparison methodologies were used to analyze the reasons for the abuse, followed by a critical methodology to criticize the negative and abusive elements in the practice. The research concludes that the assumption that polygamy constitutes a general rule of Sharíah has resulted in misconceptions on the ideal polygamous practice. It is therefore absolutely imperative for those who are put in charge of administrating the Shari'ah law on polygamy, including scholars and law makers, to address these anomalies, so that no groups within the Muslim community would continue to suffer various forms of human rights violation resulting from the irresponsible actions of those who have abused polygamy for their own vested interests and objectives, contrary to the general intents (maqasid) and spirit of Qur’anic legislations.